CONTRADICTIONS ECONOMIC GROWTH& INVESTOR EXIT IN INDONESIA - Chandra Hendriyani (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2016)
Slowing global economic growth and a decline in the level of trust business institutions in the Euro Area and the United Kingdom to Indonesia contributed to an economic slowdown in Indonesia. Although economic growth in Indonesia alone to increase, but it can not support the climate of the industry that is conducive and  increasing purchasing power, as is still needed "invisible hand" of the government to minimize the "Transaction Cost" and "Relational Contract" and wages rill employees decreased resulting in decreased demand society to product processing industry which led to the departure of some foreign companies in Indonesia. The government's economic policy issued gradually expected to accelerate Indonesia out of the "vicious circle" both economic slowdown and improve Indonesia's competitiveness, in order to spur national economic growth and a better investment. Government policy hope will support company to make their business sustainable